Bee-ing a Pollinator: Constraints, Concerns, and Challenges of Lowbush Blueberry Pollination - Ana María Quiroga-Arcila; Frédéric McCune; Valérie Fournier; Pierre Giovenazzo (International Journal of Fruit Science, 2025)
Lowbush blueberry (Vaccinium angustifolium Ait.) represents the most economically significant fruit crop in Canada. The primary production areas are in the provinces of Quebec, the Maritime provinces of Canada, and the state of Maine, USA. Effective entomophilous pollination is indispensable for achieving optimal fruit sets; however, significant challenges persist due to gaps in knowledge regarding the crop’s biology, factors influencing pollination and yield variability, optimal densities of commercial pollinators, and limitations associated with commercial pollination practices. This review systematically explores the critical components underpinning the pollination of lowbush blueberry fields in North America. The article is organized into six sections, addressing the crop’s commercial importance, its biological and pollination requirements, factors affecting pollination and yield, the efficacy and constraints of wild and commercial pollinators, and the risks inherent in commercial pollination systems. The findings identify monoculture dependence, the decline of wild pollinator populations, the increasing use of commercial pollinators, and the risks associated with managed bumble bee introduction as the primary challenges for sustainable pollination. This review underscores the indispensable role of wild pollinators in lowbush blueberry production and suggests that future research should prioritize the development of conservation strategies at the landscape level to ensure sustainability and long-term productivity.